The development of communication skills based on meaningful experiences - Vega, Sandra Milena; Mantilla Aragón, Elizabeth (Rastros Rostros, 2024)
The pedagogical project for preschool developed in the San Cristobal concentration, located in the north of Bucaramanga, was carried out with a group of 33 children under the direction of the teacher Luz Helena Barajas; its objective was to stimulate the development of communicative skills at this level, taking into account the daily experiences of the little ones that would allow them to think of new strategies in the process of meaningful learning.